2012
DOI: 10.1039/c1sm06809a
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium exchange kinetics in n-alkyl–PEO polymeric micelles: single exponential relaxation and chain length dependence

Abstract: In this communication we present first results on the chain exchange kinetics of n-alkyl-PEO polymeric micelles by time-resolved small angle neutron scattering. We found that the rate strongly depends on the alkyl-chain length and that the relaxation function almost perfectly follows the single exponential decay predicted by theory. The key achievement of this study is the experimental verification that core block polydispersity accounts for the almost logarithmic time decay in block copolymer micelles as rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
144
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(159 citation statements)
references
References 21 publications
14
144
1
Order By: Relevance
“…In contrast, the exchange rate is significantly faster at higher temperatures. These results resemble observations on self-assembled polymeric micelles, in which monomer expulsion and insertion is the rate-determining step of system dynamics (20,21). Moreover, monomer polymerization and depolymerization are reported to be the main exchange mechanism of supramolecular polymers in organic solvents (22).…”
Section: Resultssupporting
confidence: 69%
“…In contrast, the exchange rate is significantly faster at higher temperatures. These results resemble observations on self-assembled polymeric micelles, in which monomer expulsion and insertion is the rate-determining step of system dynamics (20,21). Moreover, monomer polymerization and depolymerization are reported to be the main exchange mechanism of supramolecular polymers in organic solvents (22).…”
Section: Resultssupporting
confidence: 69%
“…Similar to low‐molecular‐weight surfactants, diblock copolymers in a selective solvent exhibit a critical micellar concentration (CMC) and temperature (CMT) . In comparison to surfactant micelles, the dynamics of block copolymer micelles at equilibrium show more complex behaviors, and are affected by additional factors, such as polydispersity and accessible conformations, due to the nature of polymer chains . The micellization of diblock copolymers studied by computer simulation suggested that both the stepwise insertion–expulsion of single polymer chains and fusion/fission of whole micelles contributed to the redistribution of the micellar size to the equilibrium one .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Unimer desorption is the rate-limiting step and its activation energy barrier depends on the length of the hydrophobic block and the intermolecular interactions and steric hindrance between each component of both the head and the tail block. 2933 Increasing the hydrophobic chain length beyond certain values may lead to kinetically trapped heterogeneous aggregates. Chemically crosslinking the headgroups effectively reduces the unimer desorption kinetics and stabilizes micelle.…”
Section: Introductionmentioning
confidence: 99%